Resonance Monitoring System - Ong, Khai Woei (2017)
Resonance is a phenomenon at which the state of a system will be amplified in large amplitude of vibration. Excessive resonance is referred to failure and it can be damage to mechanical device or civil structure. This research aims to design a system to log and analyse data from the alternation of natural frequency of a structure. The vibration pick up voltage by the sensors can be amplified by certain gain and filter to produce a smooth data that is able to be measured using the oscilloscope. Signal processing technique using the simple MATLAB algorithm such as Fourier Transform analysis and time-frequency analysis will be used to further analyze the Rayleigh waves generated by the localized impact test. Eventually, a predictive maintenance device with statistical guideline can be designed to give immediate warning.